Boiling point it only takes one degree : monitoring cultural shifts in the 21st century - Barna, George; Hatch, Mark, 1960- (Ventura, CA Regal, 2001)
Includes bibliographical references.
Keywords: Twenty-first century -- forecasts; Church history -- twenty first century -- United States